Ellipsometric study of quasi-monolayer InAs embedded in GaAs at the threshold of quantum-dot formation - Lee, H; Park, YJ; Kim, EK (KOREAN PHYSICAL SOC, 2002)
Using spectroscopic ellipsometry, we measured the pseudo-dielectric function of self-assembled InAs/GaAs quantum dots at the onset of quantum-dot nucleation at room temperature. from 0.8 to 6 eV. The nominal InAs coverage varied from 1 to 2.6 monolayers (ML). In addition to a quantum-dot-related feature. we observed two transitions near 1.34 an 1.38 eV, which arose from the InAs wetting layer. We fitted the dielectric function of the InAs wetting layer in the visible range by performing a multi-layer analysis and found a strong excitonic enhancement of the E-1 peak.
Keywords: GROWTH; SPECTROSCOPY; LAYERS